Proinflammatory Effect of High Glucose Concentrations on HMrSV5 Cells via the Autocrine Effect of HMGB1 - Chu, Yuening; Wang, Yi; Zheng, Zhihuang; Lin, Yuli; He, Rui; Liu, Jun; Yang, Xuguang (Frontiers in Physiology, 2017)
Background: Peritoneal fibrosis, in which inflammation and apoptosis play crucial pathogenic roles, is a severe complication associated with the treatment of kidney failure with peritoneal dialysis (PD) using a glucose-based dialysate. Mesothelial cells (MCs) take part in the inflammatory processes by producing various cytokines and chemokines such as monocyte chemoattractant protein 1 (MCP-1) and interleukin 8 (IL-8). The apoptosis of MCs induced by high glucose levels also contributes to complications of PD. High mobility group protein B1 (HMGB1) is an inflammatory factor that has repeatedly been proven to be related to the occurrence of peritoneal dysfunction. Aim: In this study, we aimed to explore the effect and underlying mechanism of endogenous HMGB1 in high-glucose-induced MC injury. Methods: The human peritoneal mesothelial cell line, HMrSV5 was cultured in high-glucose medium and incubated with recombinant HMGB1. Cellular expression of HMGB1 was blocked using HMGB1 small interfering RNA (siRNA). Apoptosis and production of inflammatory factors as well as the potential intermediary signaling pathways were examined. Results: The major findings of these analyses were: (1) MCs secreted HMGB1 from the nucleus during exposure to high glucose levels; HMGB1 acted in an autocrine fashion on the MCs to promote the production of MCP-1 and IL-8; (2) HMGB1 had little effect on high-glucose-induced apoptosis of the MCs; and (3) HMGB1-mediated MCP-1 and IL-8 production depended on the activation of MAPK signaling pathways. In conclusion, endogenous HMGB1 plays an important role in the inflammatory reaction induced by high glucose on MCs via mitogen-activated protein kinase (MAPK) signaling pathways, but it seems to have little effect on high-glucose-induced apoptosis.